Granulocyte colony stimulating factor ameliorates radiation-induced morphological destruction of intestinal mucosa in rats - (:unkn) unknown (My University, 2008)
Objective: We aimed to evaluate whether prophylactic administration of granulocyte colony-stimulating factor (G-CSF) has a protective effect on the morphology of irradiated intestinal mucosa. Methods: Twenty-three animals were divided into 4 groups: saline-treated control and G-CSF-injected control groups, irradiated group with saline injection and irradiated and G-CSF administered group. G-CSF (100μg/kg/day) was given subcutaneously for four consecutive days. Twelve hours after the fourth injection, under anaesthesia a single pelvic dose of 14 Gy ionising radiation was given to the irradiated groups, while the control groups were not irradiated. On the fourth day of irradiation or sham-radiation, the rats were sacrificed and terminal ileum and rectum samples were removed for histological assessment of mucosal injury. Results: Terminal ileum samples from both G-CSF treated and saline-treated control groups revealed minimum scores. In the saline-treated IR group, the score was significantly elevated as compared to either control group. However, G-CSF administration preceding the irradiation, reduced the severity of mucosal damage. On the other hand, the increased scores in the rectum samples of irradiated rats treated with either saline or G-CSF were not different from each other. Conclusion: Prophylactic administration of G-CSF might reduce ionising radiation-induced mucosal destruction of the terminal ileum, but not of the rectum.
Keywords: G-CSF; Inflammation; Intestinal injury; Ionising radiation